PENGARUH PENAMBAHAN YEAST (Candida apicola) PADA SOSIS FERMENTASI DAGING DOMBA TERHADAP KUALITAS FISIK, KIMIA DAN AKSEPTABILITAS - Andry Pratama; Roostita L. Balia; Lilis Suryaningsih (AGROINTEK, 2021)
Lamb is one of the  animals livestock that is less desirable for consumption by some people because it has a distinctive flavour that affected it when were eating, called the smell is "prengus". Processing lamb into fermented sausage can remove the”prengus” smell. The addition of Candida apicola yeast to fermented sausages can improve quality and increase shelf life of product. This research aimed to find out the effect of adding Yeast Candida apicola on Physicochemical Properties and acceptability of Fermented Lamb Sausage. This research used experimental method with Completely Random Design with 3 levels of concentration factor 0,5%, 1%, 1,5% and 2%, and each treatment with 5 replication. The research showed addition of 2% yeast Candida apicola was had the best tenderness value 73.44 mm/sec/gram, 54,93% of water content, 9,21% of lipid content, 18,36% of protein content and also produced acceptability the most preferred flavour, taste and total acceptance.